The effect of sitting and soaking therapy with binahong leaf (Anredera cordifolia) decoction on perineal wound healing - Daini Zulmi; Leri Septiani; Suryani Soepardan (Universitas Airlangga, 2019)
Objective: To analyze the effect of sitting and soaking therapy with the decoction of Anredera cordifolia on the perineal wound healing in postpartum period mothers.Materials and Methods: The research method used is the Quasi-Experiment with pretest-posttest control group design, a sample of 62 primiparous postpartum period mothers with 2nd-grade perineal rupture. The sampling technique used is purposive sampling to obtain 31 respondents treated by 31 respondents. The wound healing variable was observed using the REEDA scale. The characteristic analysis is tested using Mann-Whitney statistical test, while to test the effect analysis is tested using the Wilcoxon test.Results: The results of this study in the intervention group showed 52.71% was cured after getting treatment for perineal wounds sitting and soaking therapy with the decoction of Anredera cordifolia. On the other hand, in the control group, using only clean water shows 27.90% recovered. Analysis data effect of using the decoction of Anredera cordifolia 25% containing on perineal wound healing showed results with Wilcoxon Test with value (p<0.05).Conclusion: Based on this result there is an effect of sitting and soaking therapy with the decoction of Anredera cordifolia on perineal wound healing for postpartum mothers.